2020
DOI: 10.1101/2020.12.13.422558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plastic-degrading potential across the global microbiome correlates with recent pollution trends

Abstract: Poor recycling has accumulated millions of tons of plastic waste in terrestrial and marine environments. While biodegradation is a plausible route towards sustainable management of plastic waste, the global diversity of plastic-degrading enzymes remains poorly understood. Taking advantage of global environmental DNA sampling projects, here we construct HMM models from experimentally-verified enzymes and mine ocean and soil metagenomes to assess the global potential of microorganisms to degrade plastics. By con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
(224 reference statements)
0
3
0
Order By: Relevance
“…Although there is a growing number of MAG reconstruction pipelines ( 43–49 ), a simple comparison of studies that used differing methods for MAG generation revealed that metaGEM consistently recovers more high quality genomes per sample, both from gut microbiome ( 11–13 ) and ocean ( 50–52 ) metagenomes ( Supplementary Figure S3 ). Indeed, metaGEM has already been applied in one of our recent studies to interrogate the plastic-degrading potential of the global microbiome ( 53 ). Regarding tool selection for specific tasks such as short read quality filtering, assembly, binning, etc., there are a number of published stand-alone candidate tools to choose from in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a growing number of MAG reconstruction pipelines ( 43–49 ), a simple comparison of studies that used differing methods for MAG generation revealed that metaGEM consistently recovers more high quality genomes per sample, both from gut microbiome ( 11–13 ) and ocean ( 50–52 ) metagenomes ( Supplementary Figure S3 ). Indeed, metaGEM has already been applied in one of our recent studies to interrogate the plastic-degrading potential of the global microbiome ( 53 ). Regarding tool selection for specific tasks such as short read quality filtering, assembly, binning, etc., there are a number of published stand-alone candidate tools to choose from in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a growing number of MAG reconstruction pipelines [32][33][34][35][36][37][38] , a simple comparison of studies that used differing methods for MAG generation revealed that metaGEM consistently recovers more high quality genomes per sample, both from gut microbiome [11][12][13] and ocean [39][40][41] metagenomes (Supplementary figure 3). Indeed, metaGEM has already been applied in one of our recent studies to interrogate the plastic-degrading potential of the global microbiome 42 .…”
Section: Implementation and Features Of Metagem Pipelinementioning
confidence: 99%
“…Interestingly, the isolation and characterisation of aquatic plastic degraders are less frequent 239 , which is probably related to the extra challenge that aquatic environments, such as the oceans, represent (e.g., low nutrient concentration and temperature) compared with soil and compost. In soil and compost, high nutrient availability, humidity and temperature are often conditions in which microorganisms thrive, positively impacting any potential biodegradation processes 240 .…”
Section: Plastic Degradationmentioning
confidence: 99%